Perancangan mesin packing pipa baja otomatis di PT Steel Pipe Industry of Indonesia, Tbk - Aditya Pramono; Heru Arizal; I Made Arsana (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
The use of automatic technology in the steel pipe packing process is a small part of the use of technology. There is a bottle neck or imbalance in the bundling process or pipe packing because it is still carried out by human workers with a capacity of 3000 pipe rods per work shift. Pipe packing machines sold in the market have dimensions that do not match the rooms at PT. Steel Pipe Industry of Indonesia, Tbk. The design process for this automatic pipe mill machine uses problem methods, literature studies, machine requirements analysis, design concepts, components, and investment BEP calculations. The result of this planning is a machine design that is obtained with a length of 6500 mm, width of 3852 mm, and height of 1500 mm, using a 1.5 Hp, 1000 Rpm motor. The loading simulation results using the solidworks application show the Yield Strength is 2.039e+008 N/m2. The maximum load limit is 2.9983e+007 N/m2, and the minimum load is 7.331e-004 N/m2, the cycle time of this packing machine is 5 minutes. The maximum limit of the load in the simulation above is no more than the Yield Strength of galvanized steel material so it is safe to lift 36 pipe rods in 1 bundling. And the Break Even Point can be achieved for 6 months.